Perlakuan Diskriminatif Terhadap Pengungsi Kulit Hitam Di Ukrainperlakuan Diskriminatif Terhadap Pengungsi Kulit Hitam Di Ukraina - Pattiasina, Niken Vira; Wattimena, Josina Augustina Yvonne; Hattu, Vondaal Vidya (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: When the Russian invasion of Ukraine caused thousands of refugees to seek refuge in neighboring countries, not a few of the black refugees were discriminated against and made it difficult for Ukrainian border officials to find protection. This fact illustrates the violation of Human Rights, especially for black refugees, because it is not in accordance with the 1951 Convention and the 1967 Protocol. This makes the author examine the Discriminatory Treatment of Black Refugees in Ukraine.Purposes of the Research: This study aims to examine how discriminatory treatment of black refugees can be qualified as a violation of human rights, how is the responsibility of UNHCR in dealing with the issue of refugees being discriminated againstMethods of the Research: This research is a normative juridical research by means of research conducted by collecting primary, secondary, tertiary data, obtained by using library research. The data that has been collected is analyzed systematically based on legal disciplines to achieve clarity on the issues to be discussedResults of the Research: The results obtained from this study are, discriminatory treatment of black refugees can be qualified as a violation of Human Rights because it violates the principles of Human Rights which are jus cogens, and is not in accordance with the rights of refugees as regulated in the 1951 Convention and 1967 Protocol. Then the responsibility of UNHCR (United Nations High Commissioner for Refugees) in dealing with the issue of discrimination against black refugees is coordinating with the Government of Ukraine and third countries or countries that provide asylum, in providing protection by providing facilities and ensuring that refugees are treated equally in fulfilling their rights, to find safe and appropriate shelter.